PENGARUH EFIKASI DIRI DAN PENGETAHUAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA MELALUI MOTIVASI - Puspitaningsih, Flora (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2014)
The objective of this study is to analyze the effect of self efficacyand entreprenuership knowledge on entreprenuer willing throught motivation. The population of this study are student of STKIP PGRI Tulungagung in Civies Education Program, Mathematic department and economic department that consist of 619 student. Then the sample taken are 243 student. Open and closed question are used as collecting data technique Structural Equation Modelling (SEM) is used as a method of data analysis. And use problabing sample method. The finding shows that: 1) self efficacy is not significantly effect on student motivation, 2) self efficacy effect significantly on student willing, 3) entreprenuership knowledge effect significantly on student motivation, 4) entreprenuership knowledge is not significantly effect on student entreprenuer willing, 5) motivation effect on student entreprenuer willing, 6) motivation do not fuction as mediation variable on the effect of self efficacy and entreprenuership knowledge on student willing of entreprenuer